Inflammation and histone modification in chronic pain - Jiang, Wei; Zhang, Li-Xi; Tan, Xuan-Yu; Yu, Peng; Dong, Ming (Frontiers in Immunology, 2023)
Increasing evidence suggests that epigenetic mechanisms have great potential in the field of pain. The changes and roles of epigenetics of the spinal cord and dorsal root ganglia in the chronic pain process may provide broad insights for future pain management. Pro-inflammatory cytokines and chemokines released by microglia and astrocytes, as well as blood-derived macrophages, play critical roles in inducing and maintaining chronic pain, while histone modifications may play an important role in inflammatory metabolism. This review provides an overview of neuroinflammation and chronic pain, and we systematically discuss the regulation of neuroinflammation and histone modifications in the context of chronic pain. Specifically, we analyzed the role of epigenetics in alleviating or exacerbating chronic pain by modulating microglia, astrocytes, and the proinflammatory mediators they release. This review aimed to contribute to the discovery of new therapeutic targets for chronic pain.